2018
DOI: 10.1002/chem.201801990
|View full text |Cite
|
Sign up to set email alerts
|

Deactivation of Excited States in Transition‐Metal Complexes: Insight from Computational Chemistry

Abstract: Investigation of the excited-state decay dynamics of transition-metal systems is a crucial step for the development of photoswitchable molecular based materials with applications in growing fields as energy conversion, data storage, or molecular devices. The photophysics of these systems is an entangled problem arising from the interplay of electronic and geometrical rearrangements that take place on a short time scale. Several factors play a role in the process: various electronic states of different spin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
53
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(54 citation statements)
references
References 155 publications
(266 reference statements)
1
53
0
Order By: Relevance
“…A graphical representation of the active orbitals is given in Figures S3 and S4 of the Supplementary Information. This choice of active space is the standard CAS for transition metal complexes in general [49,50] and has been successfully applied in complexes with spin crossover closely related to the ones treated here [10,64]. Since we are not after highly accurate relative energies, we have used basis sets of moderate size.…”
Section: Computational Informationmentioning
confidence: 99%
“…A graphical representation of the active orbitals is given in Figures S3 and S4 of the Supplementary Information. This choice of active space is the standard CAS for transition metal complexes in general [49,50] and has been successfully applied in complexes with spin crossover closely related to the ones treated here [10,64]. Since we are not after highly accurate relative energies, we have used basis sets of moderate size.…”
Section: Computational Informationmentioning
confidence: 99%
“…13,15,31 Theoretical calculations have assisted in assessing the viability of alternative relaxation mechanisms. [32][33][34][35][36] Initial studies concluded that a sequential relaxation mechanism involving a 3 MC should dominate, 35 but more recent studies indicate direct 3 MLCT relaxation to the 5 MC excited state may compete with the sequential mechanism. 32,33 The sensitivity of the second-order spin-orbit coupling magnitude to the specic geometry of the [Fe(bpy) 3 ] 2+ in the 3 MLCT excited state found by Sousa and coworkers 32,33 demonstrates the need for direct dynamics simulations to theoretically determine the relative importance of the direct and sequential mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Experimental progress together with increasingly advanced quantum chemical calculations and dynamics simulations have yielded a wealth of valuable insight into the ultrafast early deactivation dynamics in such complexes. [27][28][29][30][31] In the last ve years, a new ligand motif featuring strongly sigma-donating Nheterocyclic carbenes (NHCs) has been realized synthetically and demonstrated through a combination of time-resolved optical characterization and calculations to achieve dramatically improved excited state properties of iron complexes. 32,33 This has provided a promising path for development also of iron-based photosensitizers for a variety of photoinduced electron transfer applications.…”
Section: Introductionmentioning
confidence: 99%